AF-CBT for Families Experiencing Physical Aggression or Abuse Served by the Mental Health or Child Welfare System: An Effectiveness Trial. (November 2018) - Kolko, David J.; Herschell, Amy D.; Baumann, Barbara L.; Hart, Jonathan A.; Wisniewski, Stephen R.
The Partnerships for Families project is a randomized clinical trial to evaluate the effectiveness of Alternatives for Families: A Cognitive Behavioral Therapy (AF-CBT), an evidence-based treatment (EBT) for families who are at risk of or have histories of child physical abuse. Across 10 agencies whose programs were supported by referrals from the mental health or child welfare system, individual providers were randomized to receive AF-CBT training ( n = 90) in a 6-month learning community or treatment as usual (TAU; n = 92) which provided trainings per agency routine. We recruited families served by providers in the AF-CBT ( n = 122) and TAU ( n = 73) conditions and collected multiple outcomes at up to four time points (0, 6, 12, and 18 months). Using univariate tests and growth curve models, the analyses revealed that AF-CBT (vs. TAU) showed improvements in both service systems (e.g., abuse risk, family dysfunction) or one service system (e.g., threats of force, child to parent minor assault), with some outcomes showing no improvement (e.g., parental anger). These findings are discussed in relation to AF-CBT, service system, provider, and family characteristics, and training/dissemination methods that affect the delivery of an EBT for this population in community settings.